2011
DOI: 10.1007/s12028-011-9617-5
|View full text |Cite
|
Sign up to set email alerts
|

The FOUR Score Predicts Outcome in Patients After Traumatic Brain Injury

Abstract: The FOUR score is an accurate predictor of outcome in TBI patients. It has some advantages over GCS, such as all components of FOUR score but not GCS can be rated in intubated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
85
2
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 25 publications
4
85
2
11
Order By: Relevance
“…Neurological impairments are a major challenge for ICU patients and those with neurological damage. In line with other studies, the present study results indicate that FOUR is a correct predictor of mortality in ICU patients with traumatic brain injuries (1,14,19). FOUR is easy to use, and provides better information, particularly in intubated patients, and shows depth of coma in greater details compared to GCS, since it assesses brain stem reflexes and respiratory pattern (18).…”
Section: █ Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Neurological impairments are a major challenge for ICU patients and those with neurological damage. In line with other studies, the present study results indicate that FOUR is a correct predictor of mortality in ICU patients with traumatic brain injuries (1,14,19). FOUR is easy to use, and provides better information, particularly in intubated patients, and shows depth of coma in greater details compared to GCS, since it assesses brain stem reflexes and respiratory pattern (18).…”
Section: █ Resultssupporting
confidence: 90%
“…Following correct assessment, the nurse is enabled to identify neurological changes in patients, and contact medical team to begin emergency actions to improve survival outcomes (4). To provide quality patient care, nurses should be able to correctly assess the patient (19). Assessment of coma and damage to consciousness level is essential in monitoring neurology patients in the special care unit (12).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…As a result probability of in hospital mortality is higher for the lowest total FOUR score when compared with that of GCS. FOUR score has been subjected to validation studies [11][12][13][14][15][16] in different scenarios like neuro ICU, emergency departments, medical ICU, comatose stroke patients in acute stroke unit , traumatic brain injuries etc. It has been compared with GCS in these validation studies and excellent inter rater agreements have been observed.…”
mentioning
confidence: 99%